(untitled) (The Review of Diabetic Studies, 2024)
Introduction: The training based on simulation has become an important educational practice in nursing, as it improves clinical decision-making through the creation of realistic, controlled, and immersive learning environments. It enables the learners to combine the theoretical knowledge with practical skills within a safe environment, which encourages experiential learning and critical thinking. Aim of Work: The proposed study will explore how simulation-based training can affect the clinical decision-making skills, confidence, readiness to clinical practice of nurses, and delve into the ethical issues and challenges related to the implementation of the training. Methods: There was a mixed-method study, which consisted of structured questionnaires, semi-structured interviews, focus groups, and observational studies. Nursing students and practicing nurses were interviewed to evaluate the knowledge acquisition, decision-making competence and the experiential impressions of simulation-based learning. Findings: The simulation training enhanced clinical decision-making, confidence, and self-efficacy of the individuals participating in the training greatly. Formal pre- and post-training or pre- and post-hypotensive briefing improved reflective learning, whereas high-fidelity simulation was able to fill in gaps in clinical exposure and equip the nurses with more complicated patient-care situations. Such issues as ethical and resource-related also were found. Conclusion: The tool of transformational education is simulation-based learning which enhances competence, critical thinking, and professional judgment of nurses. The high-fidelity simulation incorporated as part of the nursing curriculum should provide a safe, effective, ethically responsible preparation to work in the real clinical environment.